Functional results after CO2 laser surgery compared with conventional phonosurgery - Hörmann, Karl; Baker Schreyer, Antonio; Keilmann, Annerose; Biermann, Gabriele (The journal of laryngology and otology, 1999)
Treatment of benign vocal fold lesions by the use of the CO2 laser is discussed critically. The aim of the present prospective randomized study was to examine the post-operative functional results after laser phonosurgery in comparison to those after cold phonosurgery. In total, 44 patients with benign vocal fold lesions underwent surgery. Conventional cold phonosurgery was performed in 23 patients, and 21 patients were treated by laser phonosurgery. To determine vocal function, examinations were performed preoperatively, on the second post-operative day, and one and four months post-operatively. The examinations included direct videolaryngoscopy, determination of maximal phonation, speech voice field as well as singing voice field. The results four months after surgery showed an improvement of vocal function in both treatment groups in comparison to the pre-operative findings. The improvement is only statistically significant after cold surgery.
Elektronische Reproduktion der Druckausgabe
Gesehen am 09.05.2022
Die 2 in CO2 ist tiefgestellt